IDIOM DALAM BAHASA MELAYU DIALEK KAPUAS HULU - M.Y, Julayha; Patriantoro, Patriantoro; Muzammil, AR (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract This research is motivated by the absence of comprehensive research in discribe of idiom of Malay Language dialect Kapuas Hulu. The issues discussed is how type, meaning, and function idiom of Malay Language dialect Kapuas Hulu. The aim of this study was to discribe of type, meaning, and function idiom of Malay Language dialect Kapuas Hulu. The method employed in this study was data collecting methods and data analysis methods. Data collecting techniques employed in this study were involved conversation observation technique, uninvolved conservation observation technique, provoking technique, recording technique, and technique notes. Data analysis methods with steps to transcribe data, calssify data, analyze data based on the issues discussed, and conclude the data. Based on the results of research and of the data analysis, 92 idioms were found. The findings can be seen from several point of views ie type, meaning, and function idiom; in terms of the type is divided into two types, namely full idioms (52 idioms) and semi idioms (40 idioms); the meaning of idiom is a meaning that deviates from the conceptual meaning and grammatical constituent; the use of idiom is closely related to the function of idiom that is to provide advice, to satire, to compilment, and to reinforce a statement. Keywords: type, meaning, and idiom function